Effects of Cardiovascular, Resistance and Combined Exercise Training on Cardiovascular, Performance and Blood Redox Parameters in Coronary Artery Disease Patients: An 8-Month Training-Detraining Randomized Intervention - Tryfonas Tofas; Ioannis G. Fatouros; Dimitrios Draganidis; Chariklia K. Deli; Athanasios Chatzinikolaou; Charalambos Tziortzis; George Panayiotou; Yiannis Koutedakis; Athanasios Z. Jamurtas (MDPI AG, 2021)
It is well-documented that chronic/regular exercise improves the cardiovascular function, decreases oxidative stress and enhances the antioxidant capacity in coronary artery disease (CAD) patients. However, there is insufficient evidence regarding the chronic effects of different types of training and detraining on cardiovascular function and the levels of oxidative stress and antioxidant status in these patients. Therefore, the present study aimed at investigating the effects of cardiovascular, resistance and combined exercise training followed by a three-month detraining period, on cardiovascular function, physical performance and blood redox status parameters in CAD patients. Sixty coronary artery disease patients were randomly assigned to either a cardiovascular training (CVT, N = 15), resistance training (RT, N = 11), combined cardiovascular and resistance training (CT, N = 16) or a control (C, N = 15) group. The training groups participated in an 8-month supervised training program (training three days/week) followed by a 3-month detraining period, while the control group participated only in measurements. Body composition, blood pressure, performance-related variables (aerobic capacity (VO2max), muscle strength, flexibility) and blood redox status-related parameters (thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC), reduced glutathione (GSH), oxidized glutathione (GSSG), catalase activity (CAT), protein carbonyls (PC)) were assessed at the beginning of the study, after 4 and 8 months of training as well as following 1, 2 and 3 months of detraining (DT). CVT induced the most remarkable and pronounced alterations in blood pressure (~9% reduction in systolic blood pressure and ~5% in diastolic blood pressure) and redox status since it had a positive effect on all redox-related variables (ranging from 16 to 137%). RT and CT training affected positively some of the assessed (TAC, CAT and PC) redox-related variables. Performance-related variables retained the positive response of the training, whereas most of the redox status parameters, for all training groups, restored near to the pre-exercise values at the end of the DT period. These results indicate that exercise training has a significant effect on redox status of CAD. Three months of detraining is enough to abolish the exercise-induced beneficial effects on redox status, indicating that for a better antioxidant status, exercise must be a lifetime commitment.